Same-Sex Marriage in the National Criminal Code - Cahyani, Mutiara Gita; Maskur, Muhammad Azil (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The complexity of the problems currently faced by society is related to the development of sexual behavior of same-sex intercourse. Reviewed from the health aspect, this act of intercourse has a higher risk of transmitting sexually transmitted diseases compared to general sexual behavior. In addition, this behavior is a sexual deviation that can also be used as means to commit a crime.Purposes of the Research: This study aims to identify, analyze and formulate a criminal policy on same-sex intercourse in the National Criminal Code.Methods of the Research: This research method uses a normative legal research type with a statute approach, a case approach and a conceptual approach. The legal analysis technique in this study was carried out kualitative.Results Main Findings of the Research: This study shows that the Criminal Code still has weaknesses in the elements of criminalization of perpetrators of same-sex intercourse. The weakness is that the National Criminal Code only recognizes limited intercourse only between men and women, related to same-sex indecent acts that can be subject to criminalization if carried out under certain conditions. The solution needs to be formulated to expand the norms and create specific regulations (lex specialis) related to these acts. This is to maximize criminalization not only as a repressive means but also as a preventive measure against same-sex intercourse which is categorized as a criminal act.